Fluid and particle dynamics in laser powder bed fusion - Bidare, P.; Bitharas, I.; Ward, R.M.; Attallah, M.M.; Moore, A.J. (Acta materialia, 2018)
In this work, we employ a combination of high-speed imaging and schlieren imaging, as well as multiphysics modelling, to elucidate the effects of the interaction between the laser beam and the powder bed. The formation of denuded areas where the powder was removed during single line and island scans over several layers were imaged for the first time. The inclination of the laser plume was shifted from forwards to backwards by changing power and scan speed, resulting in different denudation regimes with implications to the heat, mass and momentum transfer of the process. As the build progressed, denudation became less severe than for a single powder layer, but the occurrence of sintered and fused powder agglomerates, which were affected by the plume, increased. Schlieren imaging enabled the visualisation of the Ar gas flow, which takes place in the atmosphere above the bed due to the plume, in addition to its interaction with affected particles. Numerical modelling was used to understand and quantify the observed flow behaviour, through the hydrodynamic treatment of the laser plume as a multi-component Ar-Fe plasma. These results promote the characterisation of fluid dynamic phenomena during the laser powder-bed fusion (LPBF) process, which constitutes a key factor in the prevention of defects in additively manufactured parts. [Display omitted]